The measurement of the effectiveness of leadership styles for organizational commitment in Pakistan - Ahmad, Ashfaq; Abdul Majid, Abdul Halim; Mohd Zin, Md. Lazim (Canadian Center of Science and Education, 2015)
This paper examines the relationship between transformational and transactional leadership and organizational commitment.Survey method was used for the purpose of collecting data from academic staff working in public sector Tertiary Institutions in Pakistan.Total 200 questionnaires were collected.After the process of data analysis, the results revealed both transformational leadership styles and transactional leadership style have significant effect on organizational commitment.However, PLS modelling outcome showed that the transformational leadership style was more influencing factor on organizational commitment than transactional leadership.Besides that, conclusions were drawn and recommendations were highlighted.